POSSIBILITIES OF THE EFFECTIVE WASTE MANAGEMENT OF ORE MINING AND DRESSING GROUPS FOR THE PRODUCTION OF THE HEAVY - AGGREGATE - Nikiforova, N. A. (Science and Transport Progress, 2010)
The possibility of the effective waste management of ore mining and dressing groups for the production of the heavy-aggregate concrete is shown.